Legalitas Perusahaan Penanaman Modal Asing Untuk Mendatangkan Tenaga Kerja Asing ke Indonesia di Tengah Pandemi Covid-19 - Terry Christy Prasetya (Faculty of Law, Universitas Airlangga, 2021)
AbstractNovel Coronavirus (Covid-19) is a contagious virus which attacks the respiratory system and has swept the entire world, including Indonesia. This virus has a very high transmission rate and affects various sectors in Indonesia, such as the economic sector. The Indonesian government always strives to maintain a positive investment climate for foreign investors. With the spread of the Covid-19 virus, countries around the world have closed access to their countries. This includes Indonesia. PT. PMA Virtue Dragon Nickel Industri (VDNI), a foreign investment company in Indonesia which holds a permit from the Ministry of Manpower (KEMENAKER) to bring in foreign workers in the context of building a smelter amidst the Covid-19 pandemic. This caused a polemic in Indonesia because despite various labor problems, the Indonesian Government gave permission to bring foreign workers to Indonesia during the Covid-19 pandemic. Therefore, this paper is a juridical analysis will be carried out regarding the legality of foreign investment companies bringing in foreign workers in the middle of the Covid-19 pandemic. Keywords: Foreign Worker; Covid -19; Legality.AbstrakNovel Coronavirus (Covid-19) adalah sebuah virus menular yang menyerang sistem pernafasan yang melanda seluruh dunia tidak terkecuali di Indonesia. Dengan tingkat penularan yang sangat tinggi hal ini tentunya memperngaruhi berbagai sektor di Indonesia termasuk dalan sektor ekonomi. Pemerintah Indonesia tentunya selalu berupaya untuk menjaga iklim investasi yang positif bagi penanaman modal asing. Dengan menyebarnya virus Covid-19 negara – negara di dunia menutup akses masuk ke negaranya, temasuk Indonesia. PT. PMA Virtue Dragon Nickel Industri (VDNI) salah satu perusahaan penanaman modal asing yang ada di Indonesia dan memegang izin dari Kementerian Tenaga Kerja (KEMENAKER) untuk mendatangkan tenaga kerja asing dalam rangka pembagunan smelter ditengah pandemi Covid-19. Hal ini kemudian menimbulkan polemik di Indonesia karena ditengah berbagai permasalahan ketenagakerjaan Pemerintah Indonesia memberikan izin untuk mendatangkan Tenaga Kerja Asing ke Indonesia di tengah pandemi Covid-19. Oleh karena itu dalam penulisan ini akan dilakukan analisa yuridis mengenai legalitas perusahaan penanaman modal asing untuk mendatangkan tenaga kerja asing di tengah pandemi Covid-19Kata Kunci: Tenaga Kerja Asing; Covid-19; Legalitas.